Determinant Health Locus of Internal and External Health Locus of Control as a Predicator of Quality of Life in Type II Dm Patients In Tetunyung Village Takengon East 2021 - Zulfahri Lubis; Fitriani Fadillah (Science Midwifery, 2022)
Diabetes Mellitus (DM) is a metabolic disorder disease characterized by loss of carbohydrate tolerance. Problems with the quality of life of DM patients are quite complex problems. This will affect several aspects of life, DM conditions that are not managed properly in the long term will contribute to the occurrence of chronic complications. This will have an impact on the patient's quality of life. Decreased quality of life can affect the life expectancy of DM patients and can significantly affect the increase in mortality. This study aims to determine the determinants of internal health locus of control and external health locus of control as predictors of quality of life in type 2 diabetes patients in Tetunyung village, East Takengon in 2021. This study used a cross-sectional study design, the population in this study were Type-2 diabetes mellitus sufferers in Tetunyung Takengon Timur Village as many as 103 Type-2 DM sufferers. The sample in this study was selected by purposive sampling with the criteria of Type 2 DM sufferers with a total of 40 patients. Research instrument in the form of a questionnaire. Bivariate analysis using multiple linear regression. The results of the study found that what affects the quality of life in patients with type-2 diabetes mellitus is the internal locus of control as much as 66%. The results of calculations using the SPSS program with a p value of 0.000 (p <0.05). The conclusion in this study is that there is a relationship between locus of control and quality of life where when individuals with good locus of control will produce a good quality of life.